Ukraine’s crisis and Russia’s closest allies: A reinforced intra-alliance security dilemma at work - Vieira, Alena (2014)
Russia’s actions towards Ukraine in 2013-14, which inaugurated a new Cold War in its relations with the West, presented a dilemma to Russia’s allies: whether to align themselves with Russia’s choices or pursue a more independent course of action. The leadership of Belarus, Russia’s closest ally, chose the latter option both by establishing dialogue with the interim government and President of Ukraine, Oleksandr Turchinov, considered illegitimate in Russia and, later, by being present at the inauguration of Petro Poroshenko on 7 June 2014 and downplaying Russia’s position on the ‘federalisation’ of Ukraine as the only way out of the country’s instability. The perspective of the intra-alliance security dilemma helps explain the divergence of views between Russia and Belarus, while pointing to the changing position of the parties towards the Eurasian integration project.